The Impact of a Barrier Island Loss on Extreme Events in the Tampa Bay - Ulm, Marius; Arns, Arne; Wahl, Thomas; Meyers, Steven D.; Luther, Mark E.; Jensen, Jürgen (Frontiers in Marine Science, 2016)
Barrier islands characterize up to an eighth of the global coastlines. They buffer the mainland coastal areas from storm surge and wave energy from the open ocean. Changes in their shape or disappearance due to erosion may lead to an increased impact of sea level extremes on the mainland. A barrier island threatened by erosion is Egmont Key which is located in the mouth of the Tampa Bay estuary at the west-central coast of Florida. In this sensitivity study we investigate the impact a loss of Egmont Key would have on storm surge water levels and wind waves along the coastline of Tampa Bay. We first simulate still water levels in a control run over the years 1948-2010 using present-day bathymetry and then in a scenario run covering the same period with identical boundary conditions but with Egmont Key removed from the bathymetry. Return water levels are assessed for the control and the scenario runs using the Peak-over-threshold method along the entire Tampa Bay coastline. Egmont Key is found to have a significant influence on the return water levels in the Bay, especially in the northern, furthest inland parts where water levels associated with the 100-year return period increase between 5 cm and 15 cm. Additionally, wind wave simulations considering all 99.5th percentile threshold exceedances in the years 1980-2013 were conducted with the same control and scenario bathymetries. Assessing changes in return levels of significant wave heights due to the loss of Egmont Key revealed an increase of significant wave heights around today's location of the island.